Uji Potensi Probiotik Isolat Lactobacillus plantarum JBSxH.6.4 Asal Fermentasi Tigarun (Crateva nurvala Buch.-Ham.) Secara In Vitro - Fasha, Gusti Nur Aida; Nur, Hasrul Satria; Rahmi, Nazarni (Program Studi S1 Farmasi, STIKES Senior, Medan, 2025)
Lactobacillus plantarum JBSxH.6.4 isolate was isolated from fermented food of Tigarun (Crateva nurvala Buch.-Ham.), a traditional fermented food from Kalimantan. This study aimed to evaluate its probiotic potential through a series of in vitro tests, including hemolysis analysis, tolerance to acidic pH and bile salt, inhibitory activity against pathogenic bacteria, and interactions with nonpathogenic bacteria. The results showed that Lac. plantarum JBSxH.6.4 exhibited γ-hemolysis, confirming its non-pathogenicity. The isolate survived at pH levels of 2.0, 3.0, and 4.0, demonstrating its acid tolerance. It also exhibited resistance to 0.3% (w/v) bile salt, indicating its ability to survive in the digestive tract. Furthermore, Lac. plantarum JBSxH.6.4 inhibited the growth of Escherichia coli ATCC25922 at 8,08 ± 0,34 mm and Staphylococcus aureus ATCC25923 at 8,95 ± 0,15 mm, suggesting its antimicrobial properties. Additionally, interaction tests indicated that it did not inhibit Lactobacillus acidophilus FNCC0051, supporting its compatibility with beneficial gut microbiota. These findings suggest that Lac. plantarum JBSxH.6.4 meets key probiotic criteria and has potential applications in functional foods and health industries. Further studies, including in vivo evaluations, are recommended to confirm its efficacy and safety for human.